Analisis Pengendalian Persediaan Bahan Baku dengan Metode Economic Order Quantity Pada Klontang Coffe & Resto - Aam Widiawati; Anisa Nurlaela Sari; Delia Marjania; Eka Ashri Nurhamidah; Ujang Suherman (Manajemen Kreatif Jurnal, 2024)
The aim of this research is to find out and determine the optimal order quantity and frequency of ordering raw materials using the method Economic Order Quantity (EOQ) at Klontang Coffee & Resto. This research uses qualitative methods using data collection techniques through library research, field research including observation, interviews, documentation studies. The calculation results for Klontang Coffee & Resto based on data on raw material requirements and storage cost data as well as ordering costs using the Economic Order Quantity method are 14.4 kg, for the frequency of ordering raw materials is 0.83 orders in one year.